Experimental investigation of aerodynamic coefficients of the Holy Trinity Column in wind tunnel - Michálek Petr; Hračov Stanislav (MATEC Web of Conferences, 2020)
The analysis of the aerodynamic force coefficients of the Holy Trinity Column in Olomouc based on the experimental wind tunnel testing is presented. Two aerodynamic models corresponding to geometrical scales 1:75 and 1:150 were built using 3D-printer and tested in the smooth flow in order to define the global static wind effects. The larger model served as a reference case for the tests of the isolated column, while the model build with smaller scale enabled also the experimental examination of the influence of the closest surroundings. The comparison of the aerodynamic coefficients obtained from the testing of both models for various wind speeds confirms their similarity and interchangeability. The independence of the coefficients on Reynolds number, Re, were successfully verified and the presented coefficients were determined for Re = 2.7 105 for a large number of angles of wind attack. The significant decrease in the static wind load due to the surrounding buildings were observed. The obtained results can broaden the knowledge of wind load related to this type historical monuments and can be useful when deciding about their global maintenance, a type of remedial work or their conservation.